Pengembangan Varian Produksi dan Pelatihan Keselamatan Kerja pada Usaha Mikro Kecil Menengah Bengkel Las: Product Variants Development and Work Safety Training in Micro, Small and Medium Enterprises Welding Workshop - Atmojo, Yohanes Priyo; Hostiadi, Dandy Pramana; Susila, I Made Darma; Srinadi, Ni Luh Putri; Hilmi, Muhammad Riza; Ayu, Putu Desiana Wulaning (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Welding workshop MSMEs are businesses that make doors, light steel roofs, canopies and other materials made from aluminium and iron. Dewi Jaya Welding Workshop MSME is one of the MSMEs in the Tabanan Regency - Bali area, established in 1997. The obstacle faced by this MSME is limited production variants due to limited production equipment, which is still conventional and manual. Besides, several work safety procedures have yet to be carried out optimally. So, in the service activities, activities are proposed to provide production equipment and work safety training to improve, develop production variants, and create a safe environment for working at the Dewi Jaya Welding Workshop UMKM. The method of service activities carried out is mentoring and training. The activity results showed an increase of 2-5 product variants and succeeded in increasing 21% income. The results of the activity showed that there was an increase of 2-5 product variants and succeeded in increasing 18.28% revenue from March to Mei 2024. The new variants produced are a prayer place made of light iron and aluminum, and a kitchen set made of light iron. Income increases based on the number of orders for the new variant product types. This increase is expected to improve the welfare of the Dewi Jaya Welding Workshop MSMEs. The results of training activities show that workers and owners during production have used work safety standards. This was proven during the activity evaluation, workers used safety equipment such as gloves and welding glasses when welding.